Synthesis, characterization and selective Cu2+ recognition of novel E– and Z–stilbenophanes. Issue 1 (2nd January 2019) - Darabi, Hossein Reza; Sobhani, Leila; Rastgar, Saeed; Aghapoor, Kioumars; Amini, Saeed K.; Zadmard, Reza; Jadidi, Khosrow; Notash, Behrouz
ABSTRACT: We have demonstrated the synthesis and characterization of novel E - and Z -stilbenophanes via four reaction steps. X-ray structure analysis showed that the p-electrons of the double bonds and the oxygen atoms pointing towards the center of a cavity of Z -isomer. Both isomers recognize selectively Cu 2+ ions over other competing metal ions as measured by UV-vis titration by the detection limit 10–12 µM. The 1:1 ratio complex formation was confirmed by HRMS analysis. Theoretical calculations based on GIAO and CMAD approaches and 1 H NMR analysis confirmed the UV-vis data of Z-isomer. Graphical Abstract: